Synopsis of Croton section Barhamia subsection Barhamia (Euphorbiaceae) - Burilli, Nicolas Giovanny; Pereira, Amanda Da Paixão Noronha; Caruzo, Maria Beatriz Rossi (Phytotaxa, 2025)
Croton section Barhamia is one of the largest sections of the genus, with about 80 species found in the West Indies, Central and South America, with its greatest diversity in Brazil. Section Barhamia is subdivided into five subsections, including subsection Barhamia. During taxonomic studies of subsection Barhamia in Brazil, we came across some nomenclatural issues and delimitation inconsistencies for species belonging to the group. To establish better boundaries for the subsection, a checklist was compiled from a review of herbarium specimens, bibliographic databases and fieldwork, focusing on the most important known localities of occurrence for some species. We recognize fourteen species for the subsection: Croton adenocalyx, C. aemulus, C. betulaster, C. essequiboensis, C. glandulosodentatus, C. glutinosus, C. graomogolensis, C. guianensis, C. hircinus, C. longibracteatus, C. muscicapa, C. rhexiifolius, C. rudolphianus and C. urticifolius. Therefore, we here provide an updated list of species, including data of habitat and distribution.